I'm not sure if you made a typo or not, so I'll go over this two ways.

**Version 1**

I'm guessing that it is supposed to be 8x-2y = 0.

Substitute for x and y:

8(2) - 2(-4) = 0

16 - (-8) = 0

Since subtracting a negative number is the same as adding a positive one:

16 + 8 = 24

**Version 2**

If the problem is in fact 8x - 2y0:

8(2) - 2(-4)0

Since anything multiplied by 0 = 0, you have:

16 - 0

16

8x – 2y0 for x = 2 and y = –4

8x - 2y = 0 --- ( input both values in the equation)

8(2) - 2(-4) =0 ---- simplify it

16 +8 ---- adding both numbers

**24 Answer.**

plug in the numbers as their corresponding letter:

8(2) - 2(-4) = 0

simplify:

16 + 8

add

16 + 8 =24

Evaluate 8x–2y0 for x = 2 and y = –4.

plug in the numbers as their corresponding letter:

8(2) - 2(-4) = 0

simplify:

16 + 8

add

16 + 8 =24

To evaluate 8x-2y0, for x=2 and y=-4

Case(i): 8x-2y=0.If this is the expression you meant, then this is a straight line passing through the origin. And the evalution for x=2 and y=-4 makes the Left side, 8(2)-2(-4)=24 which is not equal to Right side. So, the point (x,y)=(2,-4) is not on the line, but out side it at a distance of :

[8(2)-(-4)]/sqrt[8^2+(-2)^2]=24/sqrt20 =2.2sqrt5

case(ii):

8x-2y^0. This expression is equivalent to 8x-2, as y^0=1.

So,The evaluation is: 8(2)-2(-4)^0=16-2*1= **14**.

Comments: 8x-2y0: The second term,2y0 is not properly expressed..So the evaluation can be done only if it is clearly expressed.